Kinerja Rantai Pasokan Kelompok Pembudidaya Ikan Kusukakoi Desa Cibolang Kaler Kecamatan Cisaat Kabupaten Sukabumi - Muhammad Agung Bilal; Amalia Nur Milla; Neneng Kartika Rini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Koi fish is the main aquatic product cultivated by farmers in Cibolang Kaler village because it has a relatively stable price and market. This study aims to determine the supplier performance system in the supply chain of the kusukakoi fish farmer group. This research is a quantitative research using descriptive methods. The sample in this study was 30 people and it was carried out in September and October 2021. The results showed that overall the parameters in the dimensions of this supplier system showed moderate where the suppliers (farmers) can be controlled directly by the Kusukakoi fish cultivator group.Â